CircRNA cRAPGEF5 inhibits the growth and metastasis of renal cell carcinoma via the miR-27a-3p/TXNIP pathway. (28th January 2020) - Chen, Qiong; Liu, Tao; Bao, Yi; Zhao, Tangliang; Wang, Jie; Wang, Hui; Wang, Anbang; Gan, Xinxin; Wu, Zhenjie; Wang, Linhui
Abstract: Circular RNAs (circRNAs) are reported to act as important regulators in cancers. CircRNA RAPGEF5 (cRAPGEF5) is derived from exons 2–6 of the RAPGEF5 gene and may promote papillary thyroid cancer progression. However, the role of cRAPGEF5 in renal cell carcinoma (RCC) remains unclear. In this study, we found cRAPGEF5 to be significantly downregulated in RCC tissues. Among 245 RCC cases, cRAPGEF5 downregulation correlated positively with aggressive clinical characteristics and independently predicted poor overall survival and recurrence-free survival. Functional assays demonstrated that cRAPGEF5 suppresses RCC proliferation and migration in vitro and in vivo . Mechanistically, RNA Immunoprecipitation and circRNA in vivo precipitation assays showed that cRAPGEF5 functions as a sponge of oncogenic miR-27a-3p, which targets the suppressor gene TXNIP. Interactions between miR-27a-3p and cRAPGEF5 or TXNIP were confirmed by dual-luciferase reporter assays. In conclusion, cRAPGEF5 plays a role in suppressing RCC via the miR-27a-3p/TXNIP pathway and may serve as a promising prognostic biomarker and novel therapeutic target for RCC patients. Highlights: cRAPGEF5 downregulation is associated with RCC progression and predicts poor prognosis in RCC. cRAPGEF5 inhibits RCC growth and metastasis by sponging miR-27a-3p. miR-27a-3p facilitates RCC proliferation and migration by regulating TXNIP. cRAPGEF5 suppresses RCC by the miR-27a-3p/TXNIP pathway.